Speech comprehension across multiple CI processor generations: Scene dependent signal processing. Issue 4 (15th June 2021) - Hey, Matthias; Böhnke, Britta; Mewes, Alexander; Munder, Patrick; Mauger, Stefan J.; Hocke, Thomas
Abstract: Objectives: In clinical practice, characterization of speech comprehension for cochlear implant (CI) patients is typically administered by a set of suprathreshold measurements in quiet and in noise. This study investigates speech comprehension of the three most recent cochlear implant sound processors; CP810, CP910, and CP1000 (Cochlear Limited). To compare sound processor performance across generations and input dynamic range changes, the state‐of‐the art signal processing technologies available in each sound processor were enabled. Outcomes will be assessed across a range of stimulation intensities, and finally analyzed with respect to normal hearing listeners. Methods: In a prospective study, 20 experienced postlingually deafened CI patients who received a Nucleus CI in the ENT department of the University Hospital of SH in Kiel were recruited. Speech comprehension was measured in quiet at 40, 50, and 65 dBSPL with monosyllabic words as well as by speech reception threshold for two‐digit numbers. In noise, speech reception thresholds were measured with the adaptive German matrix test with speech and noise in front. Results: We found that high levels of open‐set speech comprehension are achieved at suprathreshold presentation levels in quiet. However, results at lower test levels have remained mostly unchanged for tested sound processors with default dynamic range. Expanding the lower limit of the acoustic input dynamic range yields better speech comprehension at lower presentation levels. In noise the application of ForwardFocus improves the speech reception. Overall, a continuous improvement for speech perception across three generations of CI sound processors was found. Conclusions: Findings motivate further development of signal pre‐processing, an additional focus of clinical work on lower stimulation levels, and automation of ForwardFocus. Level of evidence: 2.